Insensitivity to the spatial repellent action of transfluthrin in Aedes aegypti: a heritable trait associated with decreased insecticide susceptibility. - Joseph M Wagman; Nicole L Achee; John P Grieco (Public Library of Science (PLoS), 2015)
New vector control paradigms expanding the use of spatial repellents are promising, but there are many gaps in our knowledge about how repellents work and how their long-term use might affect vector populations over time. Reported here are findings from a series of in vitro studies that investigated the plasticity and heritability of spatial repellent (SR) behaviors in Aedes aegypti exposed to airborne transfluthrin, including results that indicate a possible link between repellent insensitivity and insecticide resistance.A dual-choice chamber system was used to observe directional flight behaviors in Aedes aegypti mosquitoes exposed to passively emanating transfluthrin vapors (1.35 mg/m3). Individual SR responder and SR non-responder mosquitoes were identified, collected and maintained separately according to their observed phenotype. Subsequent testing included re-evaluation of behavioral responses in some mosquito cohorts as well as testing the progeny of selectively bred responder and non-responder mosquito strains through nine generations. At baseline (F0 generation), transfluthrin actively repelled mosquitoes in the assay system. F0 mosquitoes repelled upon initial exposure to transfluthrin vapors were no more likely to be repelled again by subsequent exposure 24 h later, but repelled mosquitoes allowed to rest for 48 h were subsequently repelled at a higher proportion than was observed at baseline. Selective breeding of SR responders for nine generations did not change the proportion of mosquitoes repelled in any generation. However, selective breeding of SR non-responders did produce, after four generations, a strain of mosquitoes that was insensitive to the SR activity of transfluthrin. Compared to the SR responder strain, the SR insensitive strain also demonstrated decreased susceptibility to transfluthrin toxicity in CDC bottle bioassays and a higher frequency of the V1016Ikdr mutation.SR responses to volatile transfluthrin are complex behaviors with multiple determinants in Ae. aegypti. Results indicate a role for neurotoxic irritation of mosquitoes by sub-lethal doses of airborne chemical as a mechanism by which transfluthrin can produce SR behaviors in mosquitoes. Accordingly, how prolonged exposure to sub-lethal doses of volatile pyrethroids might impact insecticide resistance in natural vector populations, and how already resistant populations might respond to a given repellent in the field, are important considerations that warrant further monitoring and study. Results also highlight the critical need to develop new repellent active ingredients with novel mechanisms of action.